Evaluasi Pengelolaan Air Limbah Domestik Gedung Kuliah Bersama Universitas Andalas - Saputri Sihombing, Wildani; Andika Putra, Syawal; Nur, Ansiha Ir.; Ruslinda, Yenni (Dampak, 2025)
Domestic wastewater management on university campuses is a crucial aspect of supporting sustainable development. As a center of academic and non-academic activities, Universitas Andalas produces a significant volume of domestic wastewater from the daily activities of its 31,549 academic community members as of 2023. One of its key facilities is the Shared Lecture Building complex, consisting of 10 buildings (A–J), which applies a separated wastewater management system: greywater from floor drains and washbasins is discharged directly into the nearest drainage, while blackwater from toilets is channeled into septic tanks. Currently, Universitas Andalas lacks comprehensive data and planning related to its Domestic Wastewater Management System (SPALD), despite Government Regulation No. 22 of 2021 requiring domestic wastewater to be safely treated before discharge into water bodies. This study aims to evaluate and provide recommendations for an effective and efficient SPALD, specifically for the Shared Lecture Buildings. The method used involves field observations to collect data on the existing conditions. The results show that of the 19 septic tanks observed, 36.84% did not meet vent pipe requirements, 21.05% did not follow the appropriate desludging interval, and 42.11% lacked inspection openings. Furthermore, the effluent from these septic tanks is directly discharged into drainage channels without further treatment, posing a risk of contamination to surrounding water bodies and groundwater. This study is expected to serve as a basis for improving septic tank systems in accordance with SNI 2398:2017, so that wastewater management at Universitas Andalas can operate more optimally and sustainably.   Keyword: domestic wastewater; blackwater; greywater; SPALD; Universitas Andalas